1997
DOI: 10.1152/ajpheart.1997.273.2.h981
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated neutrophils induce myosin light chain phosphorylation and isometric tension in endothelial cells

Abstract: The mechanism or mechanisms by which polymorphonuclear leukocytes (PMN) penetrate junctions between neighboring endothelial cells (EC) to traverse endothelial barriers remain unresolved. We report that chemoattractant-stimulated PMN induce a coordinate increase in both phosphorylation of serine 19 and threonine 18 of EC myosin regulatory light chains and isometric tension generation by EC monolayers. Unstimulated PMN had no effect on either parameter. These findings, coupled with our previous report (Huang et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 0 publications
5
81
2
Order By: Relevance
“…The first is based on research conducted on GPCR signaling in ECs, such as thrombin induced junctional opening 51 and postulates that leukocytes induce actomyosin contraction in ECs triggering junctional opening. [52][53][54] The second hypothesis anticipates that EC junctions are locally destabilized to allow migrating cells to squeeze through the transient opening in the junction. Recent evidence supporting the latter hypothesis shows that leukocytes trigger rapid dephosphorylation of Tyr731 on VE-cadherin via the tyrosine phosphatase SHP-2, which allows the adaptin AP-2 to bind and initiates endocytosis of VE-cadherin (Fig.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%
“…The first is based on research conducted on GPCR signaling in ECs, such as thrombin induced junctional opening 51 and postulates that leukocytes induce actomyosin contraction in ECs triggering junctional opening. [52][53][54] The second hypothesis anticipates that EC junctions are locally destabilized to allow migrating cells to squeeze through the transient opening in the junction. Recent evidence supporting the latter hypothesis shows that leukocytes trigger rapid dephosphorylation of Tyr731 on VE-cadherin via the tyrosine phosphatase SHP-2, which allows the adaptin AP-2 to bind and initiates endocytosis of VE-cadherin (Fig.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%
“…Neutrophil adhesion is known to induce a coordinate increase in endothelial cytosolic free calcium, phosphorylation of serine-19 and threonine-18 on endothelial myosin regulatory light chains, and isometric tension generation by endothelial monolayers (80,101,109,222). Neutrophilmediated outside-in endothelial signaling likely involves the same molecules that mediate neutrophil adhesion to the endothelial surface.…”
Section: Neutrophil Migration Across Vascular Endotheliummentioning
confidence: 99%
“…In a study of human microvascular endothelial monolayers, disruption of endothelial microfilaments by cytochalasin B or latrunculin A inhibits monocyte transmigration (128). On HUVEC monolayers, inhibition of myosin light-chain kinase (MLCK) diminishes neutrophil transmigration and inhibits endothelial F-actin formation, myosin filament formation, and myosin light chain (MLC) phosphorylation (101,222). As mentioned in the preceding paragraph, neutrophil adhesion to human pulmonary microvascular endothelial cells (HPMVEC) treated with TNF-␣ also leads to endothelial cell stiffening and F-actin reorganization.…”
Section: Neutrophil Migration Across Vascular Endotheliummentioning
confidence: 99%
“…While the "contraction-respreading" cycle of ECs is mainly mediated by ICAM-1/LFA-1, the detailed mechanism was not determined in the current study and requires further exploration. Previous reports have shown that ligation of ICAM-1 triggers an increase in intracellular calcium and activation of myosin light chains, MAPK, and Rho GTPase, thereby enhancing cell contraction and promoting the opening of interendothelial contacts (Hixenbaugh et al, 1997;Greenwood et al, 2003;Muller, 2003;Ley et al, 2007;Oh et al, 2007). Further studies are necessary to examine a potential involvement of these ICAM-1-mediated signaling cascades in the "contraction-respreading" cycle of ECs.…”
Section: Discussionmentioning
confidence: 95%
“…EC height was calculated by the sum of the z-axes in an orthogonal view (height of combined Z-sections) using FLUOVIEW software. (Hixenbaugh et al, 1997;Greenwood et al, 2003;Muller, 2003;Ley et al, 2007;Oh et al, 2007). In the present study, we investigated whether ICAM-1/LFA-1-mediated EC contraction is …”
Section: Introductionmentioning
confidence: 97%